Diagnosis and neurologopedic therapy in a child with sensory-motor alalia - Marta Wawrzynów (Kazimierz Wielki University, 2018)
Introduction: Alalia sensory-motor mechanism is a disorder of understanding speech, words expressing thoughts, auditory perception, shaped on the basis of physical hearing, as well as mechanisms for creating movements and create their accuracy. Alalia is dysfunction, which reveals the source of difficulty for up to 2 years of age. The reason is usually damage to the structure of the cerebral cortex, which may take place during fetal life and perinatal time. Most often alalii sensory-motor are confused with autism spectrum disorders, of both are in fact similar. Objective: The aim of the study was to develop and apply individual therapy neurologopedic alalia a child with sensory-motor and the answer to the question whether such therapy can improve speech perception and the ability of the child. Material and methods: The research method of work is an individual case study. Diagnosis was obtained from intelligence, surveillance, indicative speech testing and research neurologopedic. The result has been supplemented with the child's medical records. Results: Therapy neurologopedic brought the desired results. Results achieved in the field of manual and motor skills and eye-hand coordination. Improved memory and perception of auditory-visual and extended the time attention. Significantly enriched vocabulary. Developed the ability to play, a desire to follow suit. Improved ability to eat independently and function of organs oral-facial area. The patient became me sensitive to stimulus, more stabile, the central muscle tone has been reinforced.